Assessment of bacterial communities of black soybean grown in fields. Issue 5 (2nd November 2017) - Sugiyama, Akifumi; Unno, Yusuke; Ono, Ui; Yoshikawa, Emon; Suzuki, Hideyuki; Minamisawa, Kiwamu; Yazaki, Kazufumi
ABSTRACT: Since the domestication of soybean ( Glycine max ) about 4, 500 years ago, thousands of local cultivars have been developed around the world. In Japan, black soybeans grown in the mountainous region of central Kyoto and Hyogo prefectures, called the Tamba region, are well known for large seeds and palatability. The yields of black soybean in the Tamba region of Kyoto have decreased during the past few decades, and the involvement of rhizosphere microbes in the yield decline has been suggested. We analyzed bacterial communities of the soybean rhizosphere on 7 farms managed under different strategies. Non-metric multidimensional scaling showed shifts of bacterial communities from bulk to rhizosphere soil and the difference among the farms. The relative abundance of the Proteobacteria and Firmicutes was higher in rhizosphere soil than in bulk soil, whereas that of the Acidobacteria was higher in bulk soil. To clarify the possible relationship between bacterial communities and soybean growth, we used ConfeitoGUIplus software (version 1.2.0), based on the Confeito algorithm, which is designed to detect highly interconnected modules in a correlation network by using a unique inter-modular index with network density. One module was extracted from the rhizosphere soil community and two from bulk soil communities, suggesting the involvement of these bacteria in soybean growth.